Detecting early gastrointestinal polyps in histology and endoscopy images using deep learning - Hajsalem, Intissar Dhrari; Ayed, Yassine Ben (Frontiers in Artificial Intelligence, 2025)
IntroductionThe GastroIntestinal Cancer (GIC) is one of the most common tumors in terms of deaths and diseases. Artificial Intelligence (AI) domains such as Deep Learning (DL) have the potential to greatly improve the early identification of disease. Nevertheless, a lot of current technologies are still insufficient to detect tumors, which is why we created an approach using advanced method to identify polyps.MethodsOur three-stage deep learning-based method requires constructing an Encoder-Decoder Network (EDN) to determine the Region of Interest (ROI) in preprocessing, feature selection with pretrained models such as VGG16, VGG19, ResNet50 and InceptionV3, and Support Vector Machine (SVM) classifier to separate affected individuals from normal ones during the classification stage. Five datasets, such as CRC-VAL-HE-7K, CRC-VAL-HE-100K, Kvasir_v2, a dataset from Beijing Cancer Hospital, and a weakly labeled dataset, containing histology and endoscopic images, were utilized to train and evaluate our method.ResultsThe outcomes showed the effectiveness of our approach, with these pretrained models obtaining the best efficiency for recognizing gastrointestinal polyps. ResNet50 attained the maximum accuracy on datasets 1, 2, and 4, with performances of 97.01%, 96.49%, and 98.90%, respectively. Also, VGG16 and VGG19 performed 96.64% and 98.75% accuracy on datasets 3 and 5, respectively. However, InceptionV3 scored slightly less well than the other model.DiscussionThe advanced method produced promising results for the early detection of gastrointestinal cancer in multiple datasets.